Regulation of TLR4-associated MD-2 in intestinal epithelial cells: a comprehensive analysis - Vamadevan, Arunan S. (2009)
The intestinal epithelium maintains a state of controlled inflammation despite continuous contact with Gram-negative commensal bacteria and lipopolysaccharide (LPS) on its luminal surface. Recognition of LPS by the TLR4/MD-2 complex results in proinflammatory gene expression and cytokine secretion in intestinal epithelial cells (IEC). We have shown that IEC express low levels of MD-2 and TLR4 and are poorly responsive to LPS. In this study, we did a comprehensive analysis to understand the immune-mediated and epigenetic mechanisms by which IEC down-regulate MD-2 expression. Expression of MD-2 and TLR4 mRNA was examined in human inflammatory bowel disease and intestinal epithelial cell lines (T84, HT-29, Caco-2). Nuclear factor-κB transcriptional activation was used as a measure of LPS responsiveness. Intestinal epithelial cellsin patients with IBD exhibited increased expression of MD-2 and TLR4 mRNA. Lipopolysaccharide responsiveness in IEC was polarized to the basolateral membrane. Bisulfite sequencing of the MD-2 promoter demonstrated methylation of CpG dinucleotides. Inhibition of methylation by 5-azacytidine and histone deactylation by trichostatin A, two forms of epigenetic silencing, resulted in increased mRNA expression of MD-2 in IEC. These results demonstrate various molecular mechanisms by which IEC down-regulate MD-2 and thereby protect against dysregulated inflammation to commensal bacteria in the intestinal lumen.